COMPARATIVE ANALYSIS OF DIFFERENT TYPES OF ART THERAPY IN PSYCHO WORKING WITH DIFFICULT ADOLESCENTS - Alla Valentinovna Suvorova; Irina Valerievna Belasheva; Ella Michailovna Kozlova (Вестник Северо-Кавказского федерального университета)
Using fairy-tale therapy, projective drawing and music therapy in troubled teens demonstrates greater efficiency fairy-tale therapy, which raises more profound and persistent personality and behavioral changes.